Effects of irrigation-induced technological change in Bangladesh rice production - Ahmed, Akhter; Sampath, Rajan K. (Wiley, 1992)
This paper evaluates the welfare implications of the irrigation‐induced technological change in rice production, based on the conceptual framework of Hayami and Herdt and using a modified formulation of the problem. The analytical model used incorporates demand and supply shifts, provides exact measures of changes in consumers' and producers' surpluses, and examines the implications for distributive justice in terms of impacts on incidence and severity of poverty and inequality in income distribution. The results of the analysis suggest that irrigation‐induced technological change would significantly promote distributive justice.